Instructor presence, interactive tools, student engagement, and satisfaction in online education during the COVID-19 Mexican lockdown - Roque-Hernández, Ramón Ventura; Díaz-Roldán, José Luis; López-Mendoza, Adán; Salazar-Hernández, Rolando (Interactive learning environments, 2023)
This paper aims to present empirical evidence that supports and quantifies the relationships among the following features in a Mexican university: interactive collaboration software tools used in online classes, the perceived presence of instructors, student engagement, and student satisfaction with online classes during the COVID-19 lockdown. We collected data from 1417 participants from five different academic programs using a survey method. Data were analyzed using SPSS v25 and WarpPLS. Findings show that the interactive communication tool has a positive impact on perceived instructor presence, which also positively impacts student engagement and satisfaction. These relationships were also found to be true after analyzing each academic program. Therefore, both the interactive communication tool and the instructor play important roles in the online learning process because they positively influence student engagement and satisfaction. Our results are consistent with previous work conducted before the pandemic and contribute to understanding the teaching and learning process during the COVID-19 pandemic.